Pembinaan Pembangunan Karakter Sumber Daya Manusia Unggul Pada Masyarakat Pulau Jaloh Batam - Sunargo; Ambalegin; Poniman (Studium: Jurnal Pengabdian Kepada Masyarakat, 2022)
The development of physical resources requires mental development that emphasizes the superiority of human resources (HR). In general, the development of infrastructure as a physical resource in Batam City has been adequate to the islands around Batam such as Jaloh Island. Human resource character development needs to be improved so that infrastructure development can be utilized optimally by the community to open opportunities for excellence. The role of superior human resources is needed based on character building in order to be able to determine the potential advantages of the community. Character building is important to support the development of physical resources. The potential of the island as a local, national, and foreign tourist spot also requires the support of leadership. This community service aims to form a community with leadership and personal characters in supporting physical development, the potential of the tourist island area, and marine products. This community service was carried out to the Jaloh Island Youth Organization to obtain superior human resources. The implementation of the service started in December 2021 until June 2022 for five meetings. The method of service is through the delivery of material with presentations, discussions, and evaluations. The results showed that participants have the readiness and willingness to carry out character development to become superior human resources.